Effect of interferon on broilers’ fecal microbiome composition. - Burakova, Inna; Smirnova, Yuliya; Gryaznova, Mariya; Morozova, Polina; Kotarev, Vyacheslav; Lyadova, Ludmila; Ivanova, Nadezhda; Denisenko, Larisa; Syromyatnikov, Mikhail (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The purpose of our study was to investigate the effect of chicken interferon on the intestinal microbiota of broiler chickens. Materials and Methods: The study used next-generation sequencing on the Ion Torrent pragmatic general multicast platform to target the V3 16S ribosomal ribonucleic acid hypervariable region gene, allowing us to analyze in detail changes in the composition of the broiler chicken microbiome. Results: Forty-one bacterial genera were identified in the studied groups of broilers. The highest abundance in both groups was observed for Lactobacillus, which was 31.08% ± 6.52 in the control group and 36.08% ± 7.25 in the interferon group. There was no clustering between the microbiome communities of the groups studied. We found a decrease or complete absence of Escherichia–Shigella, Eubacterium fissicatena group, Lachnospiraceae CHKCI001, and Pediococcus in the interferon-treated broiler group compared to the control group and an increase in the number of genera Ruminococcaceae CAG-352 and Turicibacter in the interferon group. Conclusion: A decrease in E.–Shigella may indicate normalization of the intestinal microbiota of broilers, and it can also be concluded that the introduction of interferon helps to suppress opportunistic bacteria. In the interferon group, a sharp increase in the number of Turicibacter was observed. Representatives of this genus are among the most common members in the intestines of broilers. J. Adv. Vet. Anim. Res., 12(2): 487–496, June 2025 http://doi.org/10.5455/javar.2025.l914